PERSONAL LEARNING ENVIRONMENTS AND OPEN EDUCATIONAL RESOURCES IN HIGHER EDUCATION - Esteban Vázquez-Cano (Notandum, 2017)
This paper presents from a theoretical approach the didactic functionality of Personal Learning Environments (PLEs) and Open Educational Resources (OERs) in Higher Education. The combination of both didactic strategies in recent studies show that the joint use of PLEs and OERs designed by students improves their digital competence, mainly in capabilities such as: accessing and searching for online information; articulating information needs; finding relevant information; selecting resources effectively; navigating between online sources; and creating personal information strategies. Furthermore, the main benefits of the implementation of PLEs and OERs are: a student-centric approach, the development of personal knowledge management strategies and the formation of a self-regulated learning model.